A MORPHOLOGICAL STUDY OF THE PRIMARY MOTOR CORTEX IN HUMANS USING HIGH RESOLUTION ANATOMICAL MAGNETIC RESONANCE IMAGING (MRI) - Hashim, Eyesha (My University, 2014)
Myeloarchitecture is a prominent feature that can identify the primary motor and sensory areas in the cerebral cortex and is increasingly imaged in magnetic resonance imaging (MRI) studies of cortical parcellation in humans. However, MRI studies of cortical myeloarchitecture are technically difficult for two reasons: the cortex is only a few millimeters thick, and intracortical contrast due to myelin is much smaller than the overall anatomical contrast between cortical tissue and underlying white matter that is typically utilized in imaging. The research in this thesis thus presents specific MRI protocols to visualize intracortical myelin, image processing protocols to delineate the heavily myelinated cortex from the adjacent typical cortex and the application of these techniques in the precentral motor cortex to study morphology of the highly myelinated dorso-medial part, consisting of Brodmann area (BA) 4 and part of BA 6. Optimization of the MRI protocols involved determining the sequence parameters for a T1-weighted MRI sequence to obtain maximal intracortical contrast at 0.7 mm isotropic resolution in imaging time of 15 min, based on T1 differences between cortex that is myelinated (GMm) or unmyelinated (GM). As part of the optimization, T1 values were measured in the following brain tissues: GM, GMm and white matter (WM). The optimization was carried out by simulating the MRI signal for a 3D, magnetization prepared, gradient echo sequence, using the measured T1 values in the analytical signal equations. It was found that lengthening the time delay at the end of each inner phase encoding loop increased the intracortical contrast. The optimization of MRI protocols also included implementing techniques to reduce radio frequency field (B1) inhomogeneities. It was found that dividing the optimized, T1-weighted MRI with a predominantly proton density weighted image resulted in a ratio image with significantly reduced B1 inhomogeneities. The goal of the image processing protocols developed in this thesis was to visualize the variation of intracortical myelin across the precentral motor cortex and to delineate its well-myelinated dorso-medial part. The myeloarchitectonic feature that was selected to visualize the variation in intracortical myelination was the thickness of GMm in the deeper parts of the cortex relative to the cortical thickness, referred to as the proportional myelinated thickness (p). To measure p, the following processing steps were performed. The ratio image was segmented into four tissues: GM, GMm, WM and cerebrospinal fluid (CSF) using fuzzy C-means clustering technique. Using a level set approach, thickness of the cortex was determined as the distance between the outer boundaries of GM and WM and thickness of GMm or myelinated thickness (m) was determined as the distance between the outer boundaries of GMm and WM. The proportional myelinated thickness p, was calculated as follows: p= m/t. The well-myelinated dorso-medial part of the precentral cortex, referred to as Mm, was distinguishable from the adjacent cortex when the proportional myelinated thickness was projected on the outer cortical surface. The optimized MRI and image processing techniques developed in this thesis were used to investigate cortical plasticity in amputees. Two morphological features of the myeloarchitecture over Mm, the mean proportional myelinated thickness and area, were measured in four lower limb amputees and four matched controls. A comparison of these morphological features showed no statistically significant difference (p < 0.05) between the two groups.
A MORPHOLOGICAL STUDY OF THE PRIMARY MOTOR CORTEX USING MRI
Keywords: Magnetic resonance imaging; Myelin; Primary motor cortex; Human; Longitudinal relaxation time; Cortical morphology